An Ideal Observer Analysis of Visual Working Memory - Sims, Chris R; Jacobs, Robert A; Knill, David C (Psychological review, 2012)
Limits in visual working memory (VWM) strongly constrain human performance across many tasks. However, the nature of these limits is not well understood. In this article we develop an ideal observer analysis of human VWM by deriving the expected behavior of an optimally performing but limited-capacity memory system. This analysis is framed around rate-distortion theory, a branch of information theory that provides optimal bounds on the accuracy of information transmission subject to a fixed information capacity. The result of the ideal observer analysis is a theoretical framework that provides a task-independent and quantitative definition of visual memory capacity and yields novel predictions regarding human performance. These predictions are subsequently evaluated and confirmed in 2 empirical studies. Further, the framework is general enough to allow the specification and testing of alternative models of visual memory (e.g., how capacity is distributed across multiple items). We demonstrate that a simple model developed on the basis of the ideal observer analysis--one that allows variability in the number of stored memory representations but does not assume the presence of a fixed item limit--provides an excellent account of the empirical data and further offers a principled reinterpretation of existing models of VWM. (Contains 12 figures, 1 table and 6 footnotes.)